Pengembangan Media Berbasis Augmented Reality (AR) Pada Pembelajaran Biologi Kelas XI SMA Negeri 13 Pangkep - Musliadi Musliadi (UNM Journal of Biological Education, 2022)
This study is a development research that aims to produce a product in the form of media based on Augmented Reality (AR) in Circulatory System material. This development research refers to ADDIE development model which consists of five (5) stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research instruments employed instrument validation sheet, teacher’s response questionnaire, students’ questionnaires, and learning outcomes test. The sample of the study were students of grade XI at SMAN 13 Pangkep. Based on the results of data analysis, it is discovered that 1) Augmented Reality (AR)-based media in Circulatory System material meets valid criteria with a mean score of 4.8 (valid); 2) the Augmented Reality (AR)-based media in Circulatory System material meets very practical criteria based on the average result of teacher’s response of 96.08% (very positive) and the result of students’ responses 83.25% (very positive); and 3) the Augmented Reality (AR)-based media in the circulatory system material meets effective criteria with the percentage of completeness of learning outcomes by 83.73% (high). Based on the results of the study, it can be concluded that Augmented Reality (AR)-based media in Circulatory System material has met valid, practical, and effective criteria.